Electricity in Africa : The Politics of Transformation in Uganda. - Gore, Christopher (Woodbridge : Boydell & Brewer, Limited, 2017)
Examines the history of electricity provision in Africa and the effects of privatization and infrastructure changes in energy transformation, offering a critical window into development politics in African states.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books